New Therapies for Gout - Vinall, Maria (MD Conference Express, 2007)
A key objective of long-term management of gout is “cure.” This can be achieved by patient education, modification of the patient’s risk factors (diet, obesity, hypertension, lipid levels), and by maintaining tissue urate levels below the saturation point for crystal formation (serum uric acid <360 ümol/l or 6 mg/dl) [Zhang W et al. Ann Rheum Dis 2006].